1999
DOI: 10.1042/0264-6021:3430169
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the thiol-group reagent N-ethylmaleimide and neutral and basic amino acid transporter-related amino acid transport

Abstract: The neutral and basic amino acid transport protein (NBAT) expressed in renal and jejunal brush-border membranes is involved in amino acid and cystine absorption. NBAT mutations result in Type 1 cystinuria. A C-terminal myc-tagged NBAT (NBATmyc) retains the amino acid transport and protein-protein interaction properties of NBAT when expressed in Xenopus oocytes. Neutral amino acid (Ala, Phe)-cationic amino acid (Arg) heteroexchanges related to NBATmyc expression in oocytes are inactivated by treatment with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 10 publications
3
20
0
Order By: Relevance
“…Since glycerol uptake was also inhibited by pCMBS, a thiol-modifying reagent, cysteine residues, which have a thiol group, seem to play an important role in the function of the carrier, as suggested for Na ϩ -dependent D-glucose transporter 1 (SGLT1) 8) and several other carriers. [9][10][11][12][13] At the higher concentration of 40 mM (Tables 1, 2), glycerol uptake was not altered by NaCl substitution or DNP, consistent with the suggestion that the contribution of passive transport is predominant.…”
Section: Time-courses Of Glycerol Uptakesupporting
confidence: 66%
“…Since glycerol uptake was also inhibited by pCMBS, a thiol-modifying reagent, cysteine residues, which have a thiol group, seem to play an important role in the function of the carrier, as suggested for Na ϩ -dependent D-glucose transporter 1 (SGLT1) 8) and several other carriers. [9][10][11][12][13] At the higher concentration of 40 mM (Tables 1, 2), glycerol uptake was not altered by NaCl substitution or DNP, consistent with the suggestion that the contribution of passive transport is predominant.…”
Section: Time-courses Of Glycerol Uptakesupporting
confidence: 66%
“…Inhibition of L-arginine uptake in the presence of Na ϩ by L-leucine is a known phenomena of CAT family. 24 Especially, characteristic inhibition by N-ethylmaleimide (NEM), which distinguishes CAT from other L-arginine transporters such as y ϩ L, 25,26 showed that CAT is mainly responsible for transport of L-arginine into K562 cells, although incomplete inhibition by NEM suggests a minor contribution of other transporters. Thus, CAT1 could be predominantly responsible for L-arginine uptake into erythroleukemic K562 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Oocytes were washed three times in uptake buffer before measuring 65 Zn 2ϩ incorporation into single oocytes as ␥ emission. Measurement of zinc efflux was based on a method described previously (13). Fifty nanoliters of 65 ZnCl 2 at a specific activity of 6.4 Ci/ml were injected into the cytoplasm of individual oocytes.…”
Section: Methodsmentioning
confidence: 99%